HUBUNGAN PENGETAHUAN DAN SIKAP TENTANG ALAT PELINDUNG TELINGA DENGAN PENGGUNAANNYA PADA PEKERJA DI PT. X - Ragil Retnaningsih (Universitas Darussalam Gontor, 2016)
Weaving department at textile industry use machines with noise intensity >90 dB, the majority of workers do not use protective equipment because they feel uncomfortable with the tool and claims to have familiar and not bothered to work on a noisy workplace. The purpose of this study was to determine the relationship between knowledge and attitudes of the use of ear protection equipment toward workers at PT. X. This study is considered observational with cross-sectional approach. The samples were 86 workers in the weaving industry taken by using simple random sampling technique. The technique of collecting data was taken through observation and questionnaire. Data analysis was performed with the bivariate statistical test of contingency coefficient. Based on the results of statistical tests of contingency coefficient showed that there was a relationship between knowledge and attitudes of the use of ear protection equipment toward workers at PT. X, where the knowledge with the use of ear protectors with a value of p = 0.000 and r = 0389 attitude (p = 0.000) with r = 0.383. There is a relationship on the Knowledge and Attitudes of the Ear Protective Equipment Use of Workers at PT. X. Keywords: Knowledge; Attitude; The Use of Personal Protective Equipment Ear